Peran Pendamping dalam Memberikan Pelayanan pada Anak Disabilitas di Yayasan Pendidikan Dwituna Harapan Baru - Nurul Fadillah Nasution; Tuti Atika (Yayasan Literasi Sains Indonesia, 2023)
This article discusses the role of companions in providing services to children with disabilities at the Dwituna Harapan Baru Education Foundation. The existence of a companion for children with special needs has a significant meaning for the process of protection and growth. Social assistance is a strategy that greatly determines the success of community empowerment. Mentoring is also an activity that means coaching, teaching, directing which has a more connotation of mastering, controlling, and controlling. Independence in children is needed to train instincts in choosing decisions and responsibilities. For children with special needs, moving towards independence is more complicated than normal children because of the limitations they have, so there will be added value in training them. The process towards independence in these children requires a companion role in every process of child development. The purpose of this writing is as a result of the author's dedication to running PKL II at the Dwituna Harapan Baru Education Foundation. The method used is qualitative research with data collection techniques by observation and interviews. Secondary data sources for this writing are journals and literature that can support the analysis of the discussion.